Multiplex PCR and NGS-based identification of mRNA splicing variants: Analysis of BRCA1 splicing pattern as a model - Hojny, Jan; Zemankova, Petra; Lhota, Filip; Sevcik, Jan; Stranecky, Viktor; Hartmannova, Hana; Hodanova, Katerina; Mestak, Ondrej; Pavlista, David; Janatova, Marketa; Soukupova, Jana; Vocka, Michal; et al. (Gene, 2017)
Alternative pre-mRNA splicing increases transcriptome plasticity by forming naturally-occurring alternative splicing variants (ASVs). Alterations of splicing processes, caused by DNA mutations, result in aberrant splicing and the formation of aberrant mRNA isoforms. Analyses of hereditary cancer predisposition genes reveal many DNA variants with unknown clinical significance (VUS) that potentially affect pre-mRNA splicing. Therefore, a comprehensive description of ASVs is an essential prerequisite for the interpretation of germline VUS in high-risk individuals. To identify ASVs in a gene of interest, we have proposed an approach based on multiplex PCR (mPCR) amplification of all theoretically possible exon-exon junctions and subsequent characterization of size-selected and pooled mPCR products by next-generation sequencing (NGS). The efficiency of this method is illustrated by a comprehensive analysis of BRCA1 ASVs in human leukocytes, normal mammary, and adipose tissues and stable cell lines. We revealed 94 BRCA1 ASVs, including 29 variants present in all tested samples. While differences in the qualitative expression of BRCA1 ASVs among the analyzed human tissues were minor, larger differences were detected between tissue and cell line samples. Compared with other ASV analysis methods, this approach represents a highly sensitive and rapid alternative for the identification of ASVs in any gene of interest.
Keywords: protein BRCA1; lidé; Alternative splicing; NGS; multiplexová polymerázová řetězová reakce; Female; BRCA1 Protein; Mutation; izoformy RNA; Humans; Breast Neoplasms; nádory prsu; vysoce účinné nukleotidové sekvenování; mutace; Computational Biology; High-Throughput Nucleotide Sequencing; výpočetní biologie; Alternative Splicing; Multiplex Polymerase Chain Reaction; Multiplex PCR; alternativní sestřih; ženské pohlaví; mRNA splicing variant; BRCA1; RNA Isoforms